Correlation between benefit finding and caregiving abilities among family caregivers of patients with lung cancer: a network analysis - Lin, Xiaoyuan; Xie, Haidan; Chen, Ziqing; Zhao, Qi; Zhou, Xiaozhou (Frontiers in Psychology, 2024)
Objective: This study aimed to construct a network analysis model for benefit finding (BF) and caregiving abilities to clarify the interrelationships and mutual influences among different dimensions and propose nursing strategies.Methods: Convenience sampling was used to select 272 family caregivers of patients with lung cancer admitted to a tertiary hospital in Guangzhou City, China, from April 2023 to November 2023. Socio-demographic and disease characteristics questionnaire, the revised BF Scale, and the Family Caregiver Task Inventory (FCTI) were used for data collection. The R software was used to construct networks for BF and caregiving abilities, and network analysis methods were employed to identify network characteristics, core nodes, and bridge nodes.Results: In the overall network, the social relationship dimension (rs=3.04) exhibited the highest strength centrality index, followed by the family relationship dimension (rs=2.94). In addition, the social relationship dimension (rbs=0.30) had the highest bridge strength centrality index, followed by the dimension of addressing personal emotional needs (rbs=0.26).This study provides a new perspective on exploring the underlying mechanisms of interaction among different dimensions of BF and caregiving abilities in family caregivers of patients with lung cancer using network analysis. The findings suggest that healthcare professionals can improve family caregivers' social relationships, family relationships and address emotion regulation to enhance BF and caregiving abilities. Specific nursing strategies are proposed, offering new intervention targets for enhancing BF and caregiving abilities among family caregivers of patients with lung cancer.